Standing at the crossroads : stories of doubt in Renaissance Italy - Faini, Marco (Italian perspectives, 2023)
Imagined as an armed old man leaping like a locust or as a young man walking in the dark, doubt occupies a prominent place in the mental landscape of Renaissance Italians. Intriguing stories of doubters, as well as allegories and tales of doubt populated sonnets, dialogues, novelle, religious tracts, and a wealth of other vernacular texts. In an age of crisis and renewal, doubt no longer pointed to an exclusively individual condition nor was it solely the object of philosophical and theological reflections. Rather, doubt became a complex cultural object at the centre of numerous cultural strategies. Why was it so? Were Renaissance Italians especially inclined to doubt? And, if so, what were the cultural and emotional consequences of such an attitude? Resorting to a large and diverse array of literary and visual sources, Marco Faini reconstructs how doubt became a privileged tool to make sense of an increasingly complex world.